2020
DOI: 10.1002/fsn3.1639
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an iron‐fortified infant cereal to reduce the risk of iron deficiency anemia in young children in East Cameroon

Abstract: Complementary foods in Africa are often poor sources of bioavailable iron. We assessed the efficacy of iron‐fortified wheat‐based infant cereal (IC) to reduce the risk of iron deficiency anemia in children aged 18–59 months in Cameroon. A 6‐month double‐blind, cluster‐randomized controlled trial was conducted in 2017 among anemic (hemoglobin 7–11 g/dl) but otherwise healthy children. In conjunction with usual diet, children received two 50 g servings/day of a standard, micronutrient‐fortified IC (providing 3.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 57 publications
0
22
0
2
Order By: Relevance
“…Eight studies were randomised controlled trials randomised at the individual level, 14 , 35 , 37 , 44 , 46 , 47 , 48 , 50 one was a controlled clinical trial, 38 and seven were cluster-randomised controlled trials. 2 , 19 , 36 , 39 , 42 , 43 , 45 Most of the studies were done in upper or lower-middle-income countries. One study was done in a high-income country, 50 and no study was done in a low-income country.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies were randomised controlled trials randomised at the individual level, 14 , 35 , 37 , 44 , 46 , 47 , 48 , 50 one was a controlled clinical trial, 38 and seven were cluster-randomised controlled trials. 2 , 19 , 36 , 39 , 42 , 43 , 45 Most of the studies were done in upper or lower-middle-income countries. One study was done in a high-income country, 50 and no study was done in a low-income country.…”
Section: Resultsmentioning
confidence: 99%
“…Here we will focus on the specific effect of FIC. Although some clinical trials have shown some marginal effects on reducing stunting [39], we would not expect a significant effect of FIC compared to non FIC on stunting.…”
Section: Association Consumption Of Fic and Stuntingmentioning
confidence: 73%
“…The results from this study regarding improvements in anemia are in line with previous findings from recent randomized clinical trials and systematic reviews. For example, in a study involving children aged 18 to 59 months from Cameroon, children who consumed an iron-fortified infant cereal had significantly higher TA B L E 2 Mean changes in hemoglobin concentrations (g/dL) from baseline to month 6 and month 8 among 208 infants receiving micronutrient-fortified infant cereal with (INT) or without (CTL) supplemental iron baseline-adjusted mean hemoglobin levels after 6 months compared to controls (10.0 ± 1.8 versus 9.7 ± 1.4 g/dl; p = .023) and had a lower prevalence of iron-deficiency anemia (14.6% versus 53.4%; p < .001) (Ekoe et al, 2020). Moreover, in a systematic review of 18 randomized trials using iron multi-micronutrient-fortified milk and cereal food in children aged 6 months to 5 years, which observed a mean increase of 0.87 g/dl in hemoglobin levels and a 50% reduction in the risk of anemia (Eichler et al, 2012).…”
Section: Iscuss Imentioning
confidence: 99%
“…Our results are in line with a systematic review of 25 randomized controlled trials, which evaluated the effect of iron supplementation on physical growth in children and did not find a statistically significant (p > .05) positive effect of iron supplementation on any anthropometric variable (weight-for-age z-score, weight-for-height z-score, height-for-age z-score, and mid-upper arm circumference)(Sachdev et al, 2006). In contrast, results from a recent study of children aged 18 to 59 months from Cameroon indicated that anemic children receiving iron-fortified infant cereal had a very small but borderline significant higher weight gain (~50 g, p = .052) and significantly higher weight-for-age z-score compared with the control group (−0.59 versus −1.03; p = .016), although no between-group differences in height, height-for-age, and weight-for-height z-scores were observed(Ekoe et al, 2020). However, it should be noted that the population in that study was mildly to moderately undernourished at baseline, with approximately 56% of children stunted in growth (height-for-age z-scores < −2) and 25% underweight (weight-for-age z-score < −2).…”
mentioning
confidence: 96%
See 1 more Smart Citation